Agricultura Periurbana en el partido de General Pueyrredón. Aportes para el diseño de políticas públicas de desarrollo territorial sustentable - Molpeceres, María Celeste (2022)
Universal problems such as undernourishment or malnutrition were historically addressed by means of technical solutions, such as the use of agrochemicals to increase crop yields after the world wars. These proposals, aimed at intensifying agro ecosystems in order to feed a growing population, show deficiencies, resulting in new problems, such as impacts on the environment and health, as well as on the distribution of damages and benefits. The simplification of systems, their problems and solutions, exhibits great limits today, having been especially evident during the COVID-19 pandemic, which exposed the fragility of current food systems. In recent years we witnessed new significances of the problem, through the introduction of concepts such as food security and food sovereignty, which invited us to reflect on the human right to access nutritious, sufficient and adequate food, including water, and that its production does not generate risks to health and the environment. In this context, there has recently been a change in public policy decisions at the national level, aimed at promoting alternative models of production. Agroecology, as a systemic approach, promotes strategies that not only generate stability in production, but also promote synergies in other areas, such as resilience to climate change, women's empowerment or income diversification. In the General Pueyrredon District (Buenos Aires Province, Argentina), discussions regarding the social and environmental risks associated with the use of agrochemicals have been high on the local public policy agenda since 2000. In recent times there has been a change in public policy decisions associated with the development of agroecology. The local proposal aligns with decisions of national and provincial bodies. Recently, a group of farmers strengthened agroecological orchards in the General Pueyrredón District, and new channels and marketing modalities were associated with it. This thesis aims to critically and comparatively analyze the processes of joint construction of regulations and practices around the promotion of peri-urban agriculture of agroecological base and the limitation of the use of agrochemicals, as strategies of sustainable territorial development. To achieve the proposed objective, an explanatory research is proposed, under a quali-quantitative design, which is nourished by participatory methodologies. Among the main results of this research emerge issues related to: I) the regulatory framework of the activity; II) the rise of agro-ecological production; III) the sustainability of horticultural production in the General Pueyrredon District; and IV) the processes of joint construction of regulations at the local level. In the first place, from the deconstruction in terms of trajectory of the regulatory framework linked to the use of agrochemicals and the promotion of alternative models at the national, provincial and municipal levels, it comes out that, by regulating the use of agrochemicals to promoting alternative production models, the State sought to arbitrate a process marked by tensions and controversies. Critically analyzing this trajectory provides elements to understand the complex interrelationships existing inside these processes. Secondly, and as it was anticipated, in recent years a series of horticultural experiences of agroecological bases emerged in the District of General Pueyrredon. In this sense, departing from the fieldwork, these experiences were mapped and characterized during the year 2020, information that did not exist thus far. In general, although this set converges in the common rejection of the use of agrochemicals, there are shades and differences among them. Thirdly, for all actors involved in the local conflict over the use of agrochemicals, the solution is "sustainability." In order to address this issue, exploring the polysemy of senses represents an important contribution to advance in the negotiations of meanings that allow to build consensual solutions. In a complementary way, the evaluation of the sustainability of agroecological based productions makes it possible to deepen their knowledge and estimate their contribution to the sustainability of the horticultural system in general, releasing difficulties and strengths. Fourthly, on the aforementioned diagnostic basis, the propositional axis is presented. The construction of this solution responds to the local characteristics of the moment and the problems surveyed, which arise in four main areas: political, technical, economic and social. Eventually, we reflect on the results of the research in two main levels: cognitivemethodological and political-institutional. On the cognitive-methodological level, it is clear that the problem was addressed mostly without considering the visions, interests and objectives of the different actors. For much of the period studied, solutions were aimed at restricting the use of agrochemicals without proposing incentives or alternatives. In this sense, the analysis carried out provides useful elements for the design of public policies for sustainable territorial development. Finally, from the political-institutional level, it is interesting to rescue the social utility of the locally generated knowledge within these processes. At the same time, the generation of planning processes is recommended, which include participatory instances, to integrate different capacities, knowledge and experiences that allow achieving a systemic vision to enable new ways of conceiving problems and solutions to address them.